New life for plastic bags, and earth pots - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Reader Jean-Yves Clavreul has dropped us (by email) a note and photo about simple methods of retaining water and earth around young plants, to encourage their growth. Put a used plastic bag (the ones that blow around everywhere) around a plant...